A influência do contexto multimidiático na configuração atual do telejornalismo - Médola, Ana Sílvia Lopes Davi [UNESP]; Dourado, Mariana [UNESP] (My University, 2010)
The TV news, like other productions for television, are in the process of adaptation of its discursive structures and its production as a consequence of the structures of the digital systems. Focusing not only the formatting, but mainly on the routines, its possible to notice the emergence of a new dynamic of production and consumption of information. Interactivity is the resource that has mobilized the most effort in the adaptation of television companies, anticipating the trend towards a more strengthening receiver role in communication relationship, which should be intensified by the convergence of medias with the deployment of Brazilian digital TV. While this is not realized, producers encourage a forged approach of receivers, since the proposal is not fully enforceable, either because of limitations in the routine production or in the technological devices. Then, the enunciative strategy of interactivity seeks to renew the social bond between the TV news and its audience.

El noticiero, así como otras producciones de la televisión, están en el proceso de adaptación de las estructuras y de la producción discursiva por la influencia estructural de los sistemas digitales. Centrado no sólo en el texto, pero principalmente en las rutinas, es posible comprobar el surgimiento de una nueva dinámica de la producción y del consumo de la información. La interactividad es la característica que ha atraído a más esfuerzos en la adaptación de las empresas de televisión, anticipándose a la tendencia hacia un mayor fortalecimiento del papel de los receptores en la relación comunicativa, que debe ser reforzada por la convergencia de los medios de comunicación con la introducción de la televisión digital en Brasil. Aunque esto no ha ocurrido, los productores fomentan una participación de los receptores forjada, ya que la propuesta no es plenamente aplicable, sea debido a las limitaciones en la producción de rutina o en el aparato. La estrategia enunciativa de interacción búsqueda renovar el vínculo social entre la televisión y su audiencia.

Os telejornais, assim como as demais produções televisivas, estão em fase de adequação de estruturas discursivas e de produção pela influência estrutural dos sistemas digitais. Incidindo não apenas sobre a formatação, mas, principalmente, sobre as rotinas, observa-se o surgimento de uma nova dinâmica de produção e consumo de informação. A interatividade é o recurso que mais tem mobilizado esforços na adaptação das empresas de televisão, antecipando a tendência de um maior fortalecimento do papel do receptor na relação comunicativa, que deverá ser intensificada pela convergência dos meios com a implantação da TV digital brasileira. Enquanto isso não se concretiza, os produtores incentivam a aproximação forjada dos receptores, já que constitui uma proposta não plenamente executável, seja em função das limitações no âmbito da rotina de produção, seja pela limitação do dispositivo tecnológico. A estratégia enunciativa da interatividade busca, então, renovar o vínculo social entre o telejornal e seu público.
The Influence of the multimedia context in the current configuration of the TV newscast
La Influencia del contexto multimidiático en la configuración actual de la televisión
Keywords: TV newscast; Citizen journalism; Digital TV; Interactivity; Noticiero; Periodismo ciudadano; TV digital; Interactividad; Telejornalismo; Jornalismo cidadão; TV digital; Interatividade